Consumo, digestibilidade, perfil metabólico e exigências nutricionais de energia para mantença e lactação de vacas Gir e F1 Holandês x Gir em diferentes planos nutricionais - Pedro Henrique de Araujo Carvalho (2016)
The aim of this study was to determine the production parameters and metabolic, energy balance and nutritional requirements for maintenance and lactation in Gir and F1 Holsteins x Gir in the middle and end of lactation in different nutritional plans. The dry matter intake was higher F1 Holsteins x Gir, (14.87 Kg) than in the Gir (9.49 Kg) at the phase ad libitum.The F1 Holsteins x Gir showed a higher milk production corrected for 4% fat and a better feed efficiency at all phases. The feed restriction was responsible for an increase in digestibility up to 4.6% in Gir and 6.1% in F1 Holsteins x Gir. The F1 Holsteins x Gir females consumed more GE, DE and ME than Gir in all phases evaluated. The energy loss in feces was higher in F1 Hosteins x Gir, 23.77% of the GE consumed. This parameters was equivalent to 20.54 at Gir animals. The energy loss at methane and urine didnt show difference between the genetic groups, and it has been 6.17 e 3.6%, respectively. The q coefficient wanst different between the groups, and it has been 0.6752. The absence of statistical was also observed for the difference k, that it has been 56%. Also, there wasnt difference between the nutritional requirements for maintenance of the genetic groups, and it has been 101.75 Mcal/Kg de LW0,75. The energy requirements for lactation were higher for the F1 Holsteins x Gir due to the larger volume of milk produced, as there was no difference in energy requirements for production each kilogram of milk. About the animals F1 Hosteins x Gir, the feed restrictions caused an increased on energy loss as methane and on the percentage of gross energy directed to lactation, without changing the proportion of such urine loss and feces. There were no differences in energy losses as methane, feces and urine, and the higher percentage of gross energy was directed to milk production in Gir animals. The parameters to determine metabolic profile of Gir and F1 Holteins x Gir animals were within reference range. There werent effects of nutritional plan on the metabolic profile, except for the betahidroxibutirato, that even so was into the physiological acceptable limit.